Engineering T cell response to cancer antigens by choice of focal therapeutic conditions. (1st January 2019) - Shao, Qi; O'Flanagan, Stephen; Lam, Tiffany; Roy, Priyatanu; Pelaez, Francisco; Burbach, Brandon J; Azarin, Samira M; Shimizu, Yoji; Bischof, John C
Abstract: Focal thermal therapy (Heat), cryosurgery (Cryo) and irreversible electroporation (IRE) are increasingly used to treat cancer. However, local recurrence and systemic spread are persistent negative outcomes. Nevertheless, emerging work with immunotherapies (i.e., checkpoint blockade or dendritic cell (DC) vaccination) in concert with focal therapies may improve outcomes. To understand the role of focal therapy in priming the immune system for immunotherapy, an in vitro model of T cell response after exposure to B16 melanoma cell lysates after lethal exposures was designed. Exposure included: Heat (50 °C, 30 min), Cryo (−80 °C, 30 min) and IRE (1250 V/cm, 99 pulses, 50 µs pulses with 1 Hz intervals). After viability assessment (CCK-8 assay), cell lysates were collected and assessed for protein release (BCA assay), protein denaturation (FTIR-spectroscopy), TRP-2 antigen release (western blot), and T cell activation (antigen-specific CD8 T cell proliferation). Results showed IRE released the most protein and antigen (TRP-2), followed by Cryo and Heat. In contrast, Cryo released the most native (not denatured) protein, compared to IRE and Heat. Finally, IRE dramatically outperformed both Cryo and Heat in T cell activation while Cryo modestly outperformed Heat. This study demonstrates that despite all focal therapies ability to destroy cells, the 'quantity' (i.e., amount) and 'quality' (i.e., molecular state) of tumor protein (including antigen) released can dramatically change the ensuing priming of the immune system. This suggests protein-based metrics whereby focal therapies can be designed to prime the immune system in concert with immunotherapies to eventually achieve improved and durable cancer treatment in vivo .